2015
DOI: 10.1108/bfj-07-2014-0236
|View full text |Cite
|
Sign up to set email alerts
|

Best-before date – food storage temperatures recorded by Swedish students

Abstract: Access to this document was granted through an Emerald subscription provided by emeraldsrm: 468524 [] For AuthorsIf you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 17 publications
2
30
0
Order By: Relevance
“…The results of temperature evaluation indicated that 25% of the fridges in the current study were at or above the currently recommended temperature (4.4°C) (Fight, 2015, Godwin et al, 2007. Similar results were revealed by other monitoring studies of domestic refrigerators (James and Evans, 1992, Johnson et al, 1998, Sergelidis et al, 1997, Bharathirajan et al, 2012, James et al, 2008, Maktabi et al, 2013, Gilbert, 2006, Marklinder and Eriksson, 2015. Generally, while storage temperature decreases, the lag phase before growth extends, and the rate of growth decreases.…”
Section: Discussionsupporting
confidence: 87%
“…The results of temperature evaluation indicated that 25% of the fridges in the current study were at or above the currently recommended temperature (4.4°C) (Fight, 2015, Godwin et al, 2007. Similar results were revealed by other monitoring studies of domestic refrigerators (James and Evans, 1992, Johnson et al, 1998, Sergelidis et al, 1997, Bharathirajan et al, 2012, James et al, 2008, Maktabi et al, 2013, Gilbert, 2006, Marklinder and Eriksson, 2015. Generally, while storage temperature decreases, the lag phase before growth extends, and the rate of growth decreases.…”
Section: Discussionsupporting
confidence: 87%
“…Space constraints in the fridge in combination with a lack of knowledge about where to best locate certain types of foods often hinder systematic storage. Indeed, a majority of consumers fail to use storing strategies to increase food longevity in their households (Farr-Wharton et al, 2014) and have their fridges set to a higher temperature than recommended which can accelerate the decay of food products (Marklinder and Eriksson, 2015;Terpstra et al, 2005).…”
Section: Storingmentioning
confidence: 99%
“…Topics covered in past mass experiments include for example the acoustic environment in classrooms [Persson Waye et al, 2015], storage of refrigerated foods [Marklinder and Eriksson, 2015], children's and adolescents' perception of hazardous environments [Wall, 2014] and the development of autumn leaves in deciduous trees. The mass experiment of 2015 is on the decomposition of organic material in soil and its relation to climate change, studied with a newly developed, standardised method built upon the burying and weighing of tea bags [Keuskamp et al, 2013].…”
Section: The Mass Experimentsfrom Preparations To Follow-upmentioning
confidence: 99%
“…Throughout the experiment, engaged teachers play a crucial role in explaining and contextualising the experiment for the students in addition to functioning as supervisors during the data collection phase of the experiment. An encouraging indication of the quality of the data is that so far three of the mass experiments have been published in well-renowned peer reviewed journals [Randall, 2010;Persson Waye et al, 2015;Marklinder and Eriksson, 2015].…”
Section: A Word On Data Qualitymentioning
confidence: 99%